Composition and Stand Structure of Tropical Moist Deciduous Forest of Similipal Biosphere Reserve, Orissa, India - Mishra, R.K.; Upadhyay, V.P.; Nayak, P.K.; Pattanaik, S.; Mohanty, R.C. (IntechOpen, 2012)
None